Using an e-Delphi consensus technique to develop the Stressful Adverse Veterinary Events Support (SAVES) Framework - Julie Gibson; Kate White; Marnie L. Brennan (PLoS ONE, 2025)
Co-ordinated approaches to supporting veterinary practitioners in relation to adverse events are needed to mitigate associated practitioner stress and to prevent future occurrence. The overarching aim of this study was to develop a framework that could be used profession wide within the veterinary sector to support practitioners in relation adverse events (the Stressful Adverse Veterinary Events Support Framework; SAVES Framework). A three-round e-Delphi consensus approach was taken. The study used an a priori determined panel of 50 stakeholders (50% veterinary practitioners – veterinary surgeons and veterinary nurses registered in the United Kingdom, 28% individuals employed within UK organisations supporting veterinary practitioners and 22% other veterinary care stakeholders). An a priori determined consensus agreement level of ≥75% was set. Forty-six recommendations entering the first round were formulated by reviewing two sources (i) The human and veterinary healthcare literature pertaining to the provision of support for practitioners who are involved in adverse events, and (ii) Transcripts from a study by the authors that explored veterinary practitioners’ experiences of and responses to adverse events. Both sources were used to identify recommendations that may be useful to veterinary practitioners and/or highlighted gaps in the current provision of such support. Recommendations were refined by the primary researcher, through discussion with the core research group and with a wider group of stakeholders via a pretesting and pilot phase before being shared with e-Delphi panellists. Panellists were asked to indicate the degree to which they agreed with each recommendation (Likert Scale; 1 = Very strongly disagree, 7 = Very strongly agree) and were informed that indications of 6 or 7 would be considered agreement and indications of 1 or 2 would be considered disagreement. In rounds one and two, panel members were asked to provide feedback regarding the recommendations, which was (i) Used to modify the recommendations or to formulate additional recommendations, and (ii) Qualitatively analysed to generate themes of factors that may influence implementation of support for veterinary practitioners in relation to adverse events. Twenty-nine of the 46 initial recommendations (63%) reached consensus. Feasibility, a multifaceted and flexible approach and the influence of human thought and behaviour were identified as factors participants thought would influence the implementation of such support. The recommendations provide the first evidence-based guidance for specifically supporting veterinary practitioners in relation to adverse events; future work should focus on assessing their implementation and impact.